2019
DOI: 10.2147/copd.s187567
|View full text |Cite
|
Sign up to set email alerts
|

<p>Minimal clinically important difference of 3-minute chair rise test and the DIRECT questionnaire after pulmonary rehabilitation in COPD patients</p>

Abstract: BackgroundThe 3-minute chair rise test (3-minute CRT) and the Disability Related to COPD Tool (DIRECT) are two reproducible and valid short tests that can assess the benefit of pulmonary rehabilitation (PR) in terms of functional capacity and dyspnea in everyday activities.MethodsWe determined the minimal clinically important difference (MCID) of the DIRECT questionnaire and 3-minute CRT using distribution methods and anchor encroaches with a panel of eight standard tests in a cohort of 116 COPD patients who c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…13 Similarly, Lévesque et al reported a mean number of 51.9 ± 13.1 rises during the 3CRT in patients with COPD whose BODE index score was in the first favorable quartile (0-2 /10). 24 These results are consistent with the threshold of 49 rises found in the present study to predict a _ VO 2peak ≥ 15 mL/kg/minute in the present cohort. This study had several limitations.…”
Section: Discussionsupporting
confidence: 93%
“…13 Similarly, Lévesque et al reported a mean number of 51.9 ± 13.1 rises during the 3CRT in patients with COPD whose BODE index score was in the first favorable quartile (0-2 /10). 24 These results are consistent with the threshold of 49 rises found in the present study to predict a _ VO 2peak ≥ 15 mL/kg/minute in the present cohort. This study had several limitations.…”
Section: Discussionsupporting
confidence: 93%
“…This included five studies examining the 6MWT, 7-11 39 studies examining STS tests, 35 studies examining step tests 19,24, and 17 studies examining the Timed Up and Go (TUG). 17,19,24,33,42,49,50,[83][84][85][86][87][88][89][90][91][92] Ten studies examined more than one test, including four that examined STS and TUG, 17,42,48,49 four that examined two kinds of STS test, 29,32,44,45 and two studies (in three reports) that examined STS, TUG and step tests. 18,23,50 The PRISMA diagram is in Figure 1 and study characteristics are in Supplementary Tables S2-S5.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 128 full text papers screened, 84 were included (85 reports). This included five studies examining the 6MWT, 7 11 39 studies examining STS tests, 12 50 35 studies examining step tests 19 , 24 , 50 …”
Section: Resultsmentioning
confidence: 99%
“…59,60 The DIRECT has also recently demonstrated to be responsive to pulmonary rehabilitation with a MCID of ≥2 units. 61 International Journal of Chronic Obstructive Pulmonary Disease 2021:16…”
Section: Assessment Of Changementioning
confidence: 99%